Marginal gains: borderland dynamics, political settlements, and shifting centre-periphery relations in post-war Nepal. Issue 3 (3rd July 2021) - Goodhand, Jonathan; Walton, Oliver; Rai, Jayanta; Karn, Sujeet
ABSTRACT: In post-war transitions, how do centre-periphery relations change, and what is the role of actors at the margins of the state in negotiating these changes? This article explores these questions by examining Nepal's post-war transition following the 2006 Comprehensive Peace Agreement focusing on three borderland districts (Saptari, Bardiya and Dolpa). The article analyses contrasting dynamics in these districts to highlight changes in centre-periphery relations across several areas including state reform, the economy, and transitional justice. The analysis shows how post-war transitions often generate new forms of contentious politics, and how groups at the margins can push back against emerging political settlements to reshape politics at the centre. The ambiguities and contradictions inherent to these processes are explored, with state restructuring processes susceptible to elite capture, and re-balancing of power between centre and periphery also coinciding with continuing or increased divisions and inequalities within borderland regions.